Color, chlorophyll a, and suspended solids effects on Secchi depth in lakes: implications for trophic state assessment. Issue 3 (13th March 2019) - Brezonik, Patrick L.; Bouchard, R. William; Finlay, Jacques C.; Griffin, Claire G.; Olmanson, Leif G.; Anderson, Jesse P.; Arnold, William A.; Hozalski, Raymond
Abstract: Secchi depth (SD), a primary metric to assess trophic state, is controlled in many lakes by algal densities, measured as chlorophyll‐ a (chl‐ a ) concentration. Two other optically related water quality variables also directly affect SD: non‐algal suspended solids (SSNA ) and colored dissolved organic matter (CDOM, expressed as the absorption coefficient at 440 nm, a 440 ). Using a database of 1, 460 samples from 625 inland lake basins in Minnesota and two other Upper Midwest states, Wisconsin and Michigan, we analyzed relationships among these variables, with special focus on CDOM levels that influence SD values and the Minnesota SD standards used to assess eutrophication impairment of lakes. Log‐transformed chl‐ a, total suspended solids (TSS), and SD were strongly correlated with each other; log( a 440 ) had major effects on log(SD) but was only weakly correlated with log(chl‐ a ) and log(TSS). Multiple regression models for log(SD) and 1/SD based on the three driving variables (chl‐ a, SSNA, and CDOM) explained 80% of the variance in SD in the whole data set, but substantial differences in the form of the best‐fit relationships were found between major ecoregions. High chl‐ a concentrations (> 50 μg/L) and TSS (> 20 mg/L) rarely occurred in lakes with high CDOM ( a 440 > 4 m −1 ), and all lakes with a 440 > 8 m −1 had SD ≤ 2.0 m despite low chl‐ a values (<10 μg/L) in most lakes. Further statistical analyses revealed that CDOM has significant effects on SD at a 440 values > 4 m −1 . Thus, SD is not an accurate trophic state metric in moderately to highly colored lakes, and Minnesota's 2‐m SD criterion should not be the sole metric to assess eutrophication impairment in warm/cool‐water lakes of the Northern Lakes and Forest ecoregion. More generally, trophic state assessments using SD in regions with large landscape sources of CDOM need to account for effects of CDOM on SD.